MATHEMATICAL MODEL OF SUBDIVIDED HYDRAULIC CIRCUITS - Valery S. KRUTIKOV; Konstantin A. LIKHODED; Nikolay V. DIVULIN (Advanced Engineering Research)
The mathematical model of subdivided hydraulic circuits that permits calculation of the fluid distribution in all points is considered.